Naakt. - Fol, Carine; Hof ter Nederloo, Sint-Pieters-Leeuw; BBL (Bank Brussel Lambert) Brussel (Sint-Pieters-Leeuw : De Vrienden van Nederloo, 1988)
De Bruyne, Dees ; De Jong, Guy ; Desomberg, Philippe ; Dubois, Dany ; Hullebroeck, Amaat ; Mara, Pol ; Penninckx, Lucia ; Snauwaert, Jef ; Theys, Yvan ; Pion, Thibaut ; Van Den Driessche, Jan ; Vander Eycken, Robert ; Verduyn, Jaak ; Vervisch, Godfried ; Vreven, Flor ; Wittevrongel, Roger
"Naakt", Hof ter Nederloo, Sint-Pieters-Leeuw, 22 januari 1988 - 28 februari 1988
boek